Heuristic-based Optimization Approach: Cost-effective School Transportation. Issue 3 (12th June 2019) - Dragan, Dejan; Keshavarzsaleh, Abolfazl; Popović, Vlado; Jereb, Borut; Intihar, Marko
Abstract : Providing optimised routing solutions have always been a priority to maximally decrease the cost of school transport. This study aims to achieve the reduction of existing costs, generated while processing the far-free transportation of eligible pupil commuters. An optimisation problem comprises minimisation of the vehicles' costs and total travel time for all pupils. To solve this problem, the proposed heuristic algorithm is developed based on route planning dependent on changes in schools' starting times so that the vehicles can visit a bigger number of schools within one route. The algorithm has been applied for a case of the observed municipality in the EU region and successfully runs for already five years. This study differs from the others as it deploys two-mechanism procedures including (a) identification of eligible pupil commuters prior to assigning them to the bus stops and (b) figuring out the optimal assignment of beginning/ending times of lessons for selected schools that would be simultaneously obtained with the optimal driving routes and fleet. The results show that a total daily mileage of all vehicles was for almost 300 kilometres lowered compared to the previous un-optimised situation, while the total number of vehicles was reduced for almost 50%.